Efficient purification of arsenic-contaminated water using amyloid–carbon hybrid membranes. Issue 42 (10th May 2017) - Bolisetty, Sreenath; Reinhold, Noemi; Zeder, Christophe; Orozco, Monica N.; Mezzenga, Raffaele
Abstract : We show the purification of arsenic-contaminated water using amyloid fibril-based membranes, which adsorb both the arsenate (+5) and arsenite (+3) oxidation forms at efficiencies of ∼99%. Abstract : We show the purification of arsenic-contaminated water using amyloid fibril-based membranes, which adsorb both the arsenate (+5) and arsenite (+3) oxidation forms at efficiencies of ∼99%. Binding isotherms indicate that amyloid fibrils possess multiple binding residues capable of strongly adsorbing arsenic ions via metal–ligand interactions, delaying the saturation of the membrane. We also show that these membranes can be reused for several cycles without any efficiency drop, and validate our technology in purifying real contaminated ground water by removing arsenic with an efficiency as high as 99.6%. These results make this technology promising for inexpensive, efficient and low-energy removal of arsenic from contaminated water.